Chemical Genetics Reveals a Role of Squalene Synthase in TGFβ Signaling and Cardiomyogenesis. (26th August 2021) - Takemoto, Yasushi; Kadota, Shin; Minami, Itsunari; Otsuka, Shinya; Okuda, Satoshi; Abo, Masahiro; Punzalan, Louvy Lynn; Shen, Yan; Shiba, Yuji; Uesugi, Motonari
Abstract: KY02111 is a widely used small molecule that boosts cardiomyogenesis of the mesoderm cells derived from pluripotent stem cells, yet its molecular mechanism of action remains elusive. The present study resolves the initially perplexing effects of KY02111 on Wnt signaling and subsequently identifies squalene synthase (SQS) as a molecular target of KY02111 and its optimized version, KY‐I. By disrupting the interaction of SQS with cardiac ER‐membrane protein TMEM43, KY02111 impairs TGFβ signaling, but not Wnt signaling, and thereby recapitulates the clinical mutation of TMEM43 that causes arrhythmogenic right ventricular cardiomyopathy (ARVC), an inherited heart disease that involves a substitution of myocardium with fatty tissue. These findings reveal a heretofore undescribed role of SQS in TGFβ signaling and cardiomyogenesis. KY02111 may find its use in ARVC modeling as well as serve as a chemical tool for studying TGFβ/SMAD signaling. Abstract : KY02111 is a widely used small molecule that boosts cardiomyogenesis. Chemical genetics of KY02111 identified squalene synthase (SQS) as a molecular target of KY02111. By disrupting the interaction of SQS with cardiac ER‐membrane protein TMEM43, KY02111 impairs TGFβ/SMAD signaling and recapitulates the clinical mutation of TMEM43 that causes an inherited heart disease.